Penta Helix Collaboration dalam Pemberantasan Korupsi untuk Mewujudkan Good Governance di Indonesia - Kismartini Kismartini; Nina Widowati; Shabilla Putri Syaharani; Anindita Ghina Pramudita (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2022)
Eradication of corruption in Indonesia has been pursued through various efforts, but the phenomenon of corruption is still very worrying. One of the efforts is through cooperation between stakeholders so that the eradication of corruption can be carried out more comprehensively from various aspects of life. This study aims to analyze the role and cooperation of stakeholders in eradicating corruption to realize good governance in Indonesia. Secondary data sources are used in this study, in the form of the latest online news, the results of previous research published in reputable journals as well as reports from both government and private entities. The data were analyzed using domain analysis techniques, to get a general picture of the object under study that came from social issues. Based on the Penta Helix approach, it can be seen that stakeholders who play a role in eradicating corruption in Indonesia consist of the Government, Community, Private, Academic, and Mass Media. Although all stakeholders have played a role, this role has not been as expected. Likewise, collaboration between stakeholders has not been carried out optimally. Therefore, a more comprehensive study is needed to increase the role and collaboration among the stakeholders involved.